CHALLENGES OF TEACHING FOREIGN LANGUAGES TO ENGINEERING STUDENTS - Meyliyeva Gulnoza Minggirovna (Bright Mind Publishing, 2025)
Engineering students are increasingly expected to operate in global contexts, making foreign language competence essential. However, teaching languages to engineering students presents unique pedagogical challenges. This study explores the main difficulties encountered by instructors and learners, as well as the strategies used to improve foreign language education in engineering programs. Using qualitative methods, the study identifies key barriers including low motivation, curriculum mismatch, and time constraints, while also highlighting best practices such as integrating ESP (English for Specific Purposes), CLIL (Content and Language Integrated Learning), and technology-enhanced learning.
Keywords: Foreign language teaching, engineering students, ESP, CLIL, language motivation, technical education, higher education, blended learning, STEM education.